The IWH Forecasting Dashboard: From forecasts to evaluation and comparison - Katja Heinisch; Christoph Behrens; Jörg Döpke; Alexander Foltas; Ulrich Fritsche; Tim Köhler; Karsten Müller; Johannes Puckelwald; Hannes Reichmayr (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2023)
The paper describes the "Halle Institute for Economic Research (IWH) Forecasting Dashboard (ForDas)". This tool aims at providing, on a non-commercial basis, historical and actual macroeconomic forecast data for the Germany economy to researchers and interested audiences. The database renders it possible to directly compare forecast quality across selected institutions and over time. It is partly based on data collected in the DFG-funded project "Macroeconomic Forecasts in Great Crises".
Keywords: 330; Wirtschaftsprognose; Datenbank; Deutschland